Keep Up the Good Work… or Else! Exploring Supervisor Responses to Quiet Quitting - Henry, Sarah E.; Bolino, Mark C.; Whitney, Jacob M. (Human Resource Management, 2025)
ABSTRACT A Google search of “quiet quitting” yields over 350 million results, which is remarkable given that the term is only a few years old. Although quiet quitting is a relatively new trend, the concept it describes—an employee's conscious decision to do the bare minimum in their job rather than going above and beyond—is familiar to researchers who have investigated organizational citizenship behavior (OCB). However, for those interested in the effective management of human resources, what is important—yet unknown—is how managers respond to employees who engage in quiet quitting. Therefore, in this conceptual paper, we use attribution theory to explore supervisor responses to employees who engage in quiet quitting and subsequently withhold OCB. We propose that supervisors will generally have negative reactions to employees' withholding OCB, but we further explain how evaluations of locus, controllability, and stability and principles of discounting and augmenting influence supervisor attributions. Finally, implications for human resource theory, research, and practice are discussed.